2009
DOI: 10.1021/jp900843x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Extended Isotropic Periodic Sum and Particle Mesh Ewald Methods for Simulations of Lipid Bilayers and Monolayers

Abstract: 3D-IPS/DFFT is an extension of the three dimensional Isotropic Periodic Sum (3D-IPS) for evaluation of electrostatic and Lennard-Jones interactions in heterogeneous systems; it utilizes a discrete fast Fourier transform (DFFT) for efficient calculation of the IPS potential with a large local region radius. The method is demonstrated to be highly accurate for simple bulk fluids, liquid/liquid and liquid/vapor interfaces, and lipid bilayers and monolayers. Values for rC (the cutoff distance for direct evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 36 publications
5
63
0
Order By: Relevance
“…Venable et al applied IPS/DFFT and PME methods for simulations of lipid bilayers and monolayers (Venable, Chen et al 2009). The method is demonstrated to be highly accurate for simple bulk fluids, liquid/liquid and liquid/vapor interfaces, and lipid bilayers and monolayers (Klauda, Wu et al 2007).…”
Section: Lipid Bilayer Systemmentioning
confidence: 99%
“…Venable et al applied IPS/DFFT and PME methods for simulations of lipid bilayers and monolayers (Venable, Chen et al 2009). The method is demonstrated to be highly accurate for simple bulk fluids, liquid/liquid and liquid/vapor interfaces, and lipid bilayers and monolayers (Klauda, Wu et al 2007).…”
Section: Lipid Bilayer Systemmentioning
confidence: 99%
“…lipid bilayers) is troublesome since the assumption that g(r) is equal to unity beyond the cutoff inherently assumes that the system is homogeneous and isotropic, something that most definitely is not true for these systems. The implication of this for simulations containing lipid bilayers has not been given much attention in the past, but coupled to the development of alternative ways of treating long-range LJ interactions [10][11][12][13][14][15][16][17] the problem has started to become more apparent the last few years. In light of this, we recently presented an implementation in the Gromacs simulation package where the PME method was used to calculate long-range LJ interactions.…”
Section: Introductionmentioning
confidence: 99%
“…28,30 The IPS method makes long-ranged nonbonded interactions short-ranged so that they can be calculated as simply as with a cutoff method. Therefore, the IPS method has the accuracy of lattice sum methods and can be calculated as efficiently as the cutoff methods.…”
Section: Introductionmentioning
confidence: 99%
“…For heterogeneous systems, the discrete fast Fourier transform accelerated 3D IPS (3D IPS/DFFT) method 29 provides an efficient way to allow a local region large enough to contain the heterogeneity of a simulation system, for a more accurate calculation of longranged interactions. Venable and co-workers 30 have compared 3D-IPS/DFFT with PME and demonstrated that this method is highly accurate for simple bulk fluids, liquid/liquid, and liquid/vapor interfaces, as well as lipid bilayers and monolayers. For lipid monolayers, 3D-IPS/DFFT is recommended over PME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation